2017
DOI: 10.1002/erv.2519
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Treatment Outcomes and Dropout Risk in Men and Women with Eating Disorders

Abstract: This study compared treatment outcomes between men and women with eating disorders (EDs) and analysed clinical predictors of treatment outcome. Our sample consisted of 131 male and 131 female ED patients who underwent cognitive behavioural therapy treatment. ED severity, personality and psychopathology were assessed using standard instruments. We found that the risk of dropout was higher for men with bulimia nervosa (BN) than for women with BN and that men with BN and other specified feeding and EDs were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 38 publications
7
48
0
2
Order By: Relevance
“…With the absence of further notable gender differences, our results fall in line with the main conclusion from the literature search that men and women with AN present comparably and that gender unspecific treatment programs help both groups in similar ways. Accordingly, our findings concur with other studies that reported similar phenotypes at admission and treatment outcomes for men and women (e.g., Agüera et al, ; Smith et al, ). This situation seems favourable for male patients, as there is some evidence that incidence rates of AN increase in men (Javaras et al, ) and rising number of male cases are hospitalized for specialized treatment (Holland, Hall, Yeates, & Goldacre, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With the absence of further notable gender differences, our results fall in line with the main conclusion from the literature search that men and women with AN present comparably and that gender unspecific treatment programs help both groups in similar ways. Accordingly, our findings concur with other studies that reported similar phenotypes at admission and treatment outcomes for men and women (e.g., Agüera et al, ; Smith et al, ). This situation seems favourable for male patients, as there is some evidence that incidence rates of AN increase in men (Javaras et al, ) and rising number of male cases are hospitalized for specialized treatment (Holland, Hall, Yeates, & Goldacre, ).…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, studies on gender effects in AN might include male subsamples that are actually atypical for this gender. This selection bias might also underlie the common finding, replicated by our study, that men and women with AN present similarly and benefit equally from specialized treatment (Agüera et al, ; Bean et al, ; Strober et al, ). Reports of specific male AN characteristics, for example, a drive for muscularity rather than thinness (Murray et al, ) and higher impulsivity (Tchanturia et al, ), are a reminder that the apparent gender‐similarity in AN needs to be interpreted with caution and that more research is needed to reveal what might be a “male” subtype of AN.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Available evidence also suggests that men may be less likely to seek treatment (Striegel, Bedrosian, Wang, & Schwartz, ), less likely to be diagnosed with an eating disorder even when presenting with identical symptoms as women (Currin, Schmidt, & Waller, ), and less likely to access treatment even with similar clinical severity (Austin et al, ). When they do access psychological treatment, men may be at higher risk for attrition than women (Agüera et al, ). Eating disorders occur across the lifespan. …”
Section: Truth 5: Eating Disorders Affect People Of All Genders Agesmentioning
confidence: 99%
“…When examined more closely, however, relapse rates following CBT for EDs are greater than 30% (Södersten et al, ). Multiple studies have also found approximately 25% of participants enrolled in clinical trials of CBT for BN and/or BED discontinue treatment prematurely (Agüera et al, ; Grilo, Masheb, Wilson, Gueorguieva, & White, ; J. R. Shapiro et al, ). Such findings suggest significant room for improvement in treatment acceptability and outcome for BN and BED.…”
Section: Introductionmentioning
confidence: 99%